Priawan: Indonesian male transgenders - Dwi Prasetyo; Diah Ariani Arimbi; Sharyn Graham Davies; Mein Woei Suen; Myrtati Dyah Artaria (Faculty of Social and Political Science, Universitas Airlangga, 2019)
There have been cases of male transgender in Indonesia, yet there is a small study about them. Why do some biological females claim their identity as male transgender? How do they think of themselves as male transgender? The researcher study their life history and how they see themselves as male transgender. We have a total of six research subjects who acknowledged themselves as male transgender. This research used the in-depth interview for gathering data within six months. The results found that they became transgender based on their desire rather than coercion from others. Some of them were comfortable in coming out to their family, but most were considering how the society would judge them, and how they might bring shame to the family. Three research subjects were not able to show their true identity as transgender, because of several considerations, such as the fear of being ostracized by the society and the fear to be eliminated from their family. They took the gender role according to what would be accepted by the current environment. We conclude that the existence of transgender, who is biologically females to become males are very reluctant to open their sexual identity because of this reason.